ANALISIS ASUHAN KEPERAWATAN PADA REMAJA DENGAN GANGGUAN POLA TIDUR MELALUI INTERVENSI SLEEP HYGIENE DAN TERAPI RELAKSASI OTOT PROGRESIF DI CLUSTER SUMUR BATU - Ega Shafira Pradanawati (2022)
Sleep is a basic human need to rebuild the body's energy. Teenagers need 8-10 hours of sleep a night. Adolescents who have sleep disorders result in cognitive decline, loss of concentration, and unstable emotions and are at risk for obesity and depression. The purpose of this study is to provide family nursing care, especially for adolescents with disturbed sleep patterns. The subjects of this study were two teenagers with problems with sleep patterns. The measuring instrument of this study was the Pittsburgh Sleep Quality Index questionnaire. The intervention used is sleep hygiene with progressive muscle relaxation therapy performed 30 minutes before bedtime for 7 days. Based on the last evaluation, there was a difference in sleep quality scores before and after the intervention, namely in managed adolescents, the score was 13 to 3, while the resumed adolescent was a score of 12 to 4. So, adolescents can apply sleep hygiene with progressive muscle relaxation therapy in overcoming sleep pattern disorders.